The path of terror attacks - Jo\~ao Ricardo Faria; Daniel G. Arce M. (Games, 2021)
This paper derives a dynamic path of ongoing terror attacks as a function of terrorists' capacity and a target government's counterterror capacity. The analysis provides several novel insights and characterizations. First, the effect of counterterror policy is limited. Second, proactive counterterror policy affects the depreciation (fatigue) of terrorists' capacity, and defensive counterterror policy limits the worst-case scenario. Third, fluctuations in the time path of attacks are a function of terrorists' time preferences and adjustment costs of changing tactics, which are policy invariant. Indeed, in our model, the oscillations of terror attacks occur irrespective of the government's counterterror stance. Fourth, collective action inefficiencies associated with the underprovision of proactive counterterror policies and overprovision of defensive ones are further exacerbated by our finding that proactive counterterror policy is the more effective of the two. Hence, the more effective policy is underprovided.
Keywords: 330; asymmetric conflict; conflict dynamics; counterterror policy; terror cycles; terror paths